Acute motor axonal neuropathy developing during Helicobacter pylori Infection - Gödekmerdan, Ahmet; Çitak Kurt, Ayşgül Neşe; Kurt, Abdullah; Kabakuş, Nimet (My University, 2004)
[Abstract Not Available]
Keywords: amoxicillin; immunoglobulin; immunoglobulin G antibody; metronidazole; omeprazole; abdominal pain; adolescent; article; bacterial infection; case report; disease association; gastrointestinal symptom; Guillain Barre syndrome; Helicobacter infection; Helicobacter pylori; human; indigestion; male; muscle weakness; nausea; nerve conduction; nerve fiber; neuropathy; peptic ulcer